2023
DOI: 10.1136/bmjopen-2022-067788
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the prevalence and correlates of multimorbidity in middle-aged men and women: a cross-sectional population-based study in four African countries

Abstract: ObjectivesTo determine the prevalence of multimorbidity, to identify which chronic conditions cluster together and to identify factors associated with a greater risk for multimorbidity in sub-Saharan Africa (SSA).DesignCross-sectional, multicentre, population-based study.SettingSix urban and rural communities in four sub-Saharan African countries.ParticipantsMen (n=4808) and women (n=5892) between the ages of 40 and 60 years from the AWI-Gen study.MeasuresSociodemographic and anthropometric data, and multimorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…34,35 The prevalence of multimorbidity in PLHIV ranges from 16% to 75% depending on the definition employed. 6,10,23,[36][37][38] Other than being at a higher risk of coinfections and opportunistic infections, PLHIV also experience accelerated aging due to the complex interaction between the patient's lifestyle, ongoing inflammation despite good virological control, and toxicity from ART. However, the exact underlying mechanisms resulting in accelerated aging remain to be elucidated.…”
Section: Multimorbidity In Older People Living With Hivmentioning
confidence: 99%
See 2 more Smart Citations
“…34,35 The prevalence of multimorbidity in PLHIV ranges from 16% to 75% depending on the definition employed. 6,10,23,[36][37][38] Other than being at a higher risk of coinfections and opportunistic infections, PLHIV also experience accelerated aging due to the complex interaction between the patient's lifestyle, ongoing inflammation despite good virological control, and toxicity from ART. However, the exact underlying mechanisms resulting in accelerated aging remain to be elucidated.…”
Section: Multimorbidity In Older People Living With Hivmentioning
confidence: 99%
“…Older PLHIV, despite being virally suppressed, exhibit higher multimorbidity rates at a younger age compared with HIV-uninfected peers. 6,7 Having multiple comorbidities simultaneously increases the likelihood of polypharmacy. Research indicates that in older PLHIV, the burden of multimorbidity and polypharmacy is more linked to the duration of HIV infection than to advanced age itself.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In developing countries multimorbidity tends to be more prevalent among the wealthier population, while in developed countries it is higher among the poor. Combinations of MCC varies across nations for example in China [ 12 ] hypertension with hearing impairment, and in Africa [ 13 ] dyslipidemia with hypertension are a few. Characterizing the patterns is a primary step to plan need-based interventions for specific populations.…”
Section: Introductionmentioning
confidence: 99%
“…14 In South Africa, an upper middle-income country, 15 despite limitations, a growing body of literature has sought to characterise the epidemiology and consequences of multimorbidity in the country. [16][17][18][19][20] Our project consisted of a systematic review of prevalence studies on multimorbidity, 21 which informed, and was followed up by the systematic analyses of the three most recent national health surveys. [22][23][24] The systematic review found a paucity of local studies and a lack of standardization of studies reporting multimorbidity estimates.…”
Section: Introductionmentioning
confidence: 99%